Bladder paraganglioma, gastrointestinal stromal tumor, and SDHB germline mutation in a patient with Carney-Stratakis syndrome: A case report and literature review - Shi, Yihang; Ding, Li; Mo, Chengqiang; Luo, Yanji; Huang, Shaoqing; Cai, Shirong; Xia, Yanzhe; Zhang, Xinhua (Frontiers in Oncology, 2022)
Background Carney-Stratakis syndrome (CSS) is a rare dyad of paraganglioma (PGL)/pheochromocytoma (PHEO) and gastrointestinal stromal tumor (GIST). PGLs are neuroendocrine tumors of neural crest origin which are mostly found in the head, neck, and retroperitoneal space. GISTs are the most common mesenchymal tumors of the digestive tract, usually caused by KIT/PDGFRA mutations. Here, we reported a case of CSS with unusual bladder PGL and succinate dehydrogenase (SDH) deficient GIST due to a germline mutation in SDH-subunit B (SDHB) gene. Case presentation A 39-year-old female patient initially diagnosed with gastric GIST and isolated pelvic metastasis was eventually found to be CSS with bladder PGL and SDH-deficient GIST after surgery. This patient underwent resection of gastric and bladder tumors, and postoperative pathology confirmed the diagnosis of CSS. According to the next-generation sequencing (NGS), the patient carried a germline mutation in the SDHB gene, which was the cause of the disorder. The patient had no tumor recurrence with regular follow-up in 10 months. Conclusions CSS is an autosomal genetic disorder with no gender difference in incidence, and PGLs are more frequent than GISTs. SDH germline mutation is the molecular biological mechanism of CSS while the most common type is SDHB mutation. The unique mechanism of tumorigenesis including hypoxia and hypermethylation caused by SDH deficiency renders target therapy with tyrosine kinase inhibitors ineffective, therefore complete surgical resection is the optimal treatment in the absence of tumor metastases.